2015
DOI: 10.5601/jelem.2014.19.2.675
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heavy metals on the activity of dehydrogenases, phosphatases and urease in naturally and artificially contaminated soils

Abstract: Most of the processes occurring in soil are catalysed by enzymes. As a result of their sensitivity towards heavy metals, enzymes in contaminated soils are usually less active. The purpose of this paper was to assess the influence of bioavailable forms of Cd, Cu, Pb and Zn on the activity of dehydrogenases, urease, acid and alkaline phosphatase, and to compare the results obtained from naturally and artificially contaminated soils. A pot experiment was carried out on two loamy sand soils, naturally and artifici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 13 publications
3
8
1
1
Order By: Relevance
“…Although low, significant negative correlations were found between alkaline phosphatase activity values and leachable Zn and Pb contents in mine soil (|R| = 0.88 (p b 0.20) and |R| = 0.85 (p b 0.20), respectively). Similar concentrations of Zn and Cd have been reported to inhibit this enzyme activity to the same levels for most of the different soil texture types subjected to evaluation, whereas some higher concentrations are required in the case of Pb (Doelman and Haanstra, 1989;Wiatrowska et al, 2015). Mine soil Zn and Pb concentrations were about two orders of magnitude higher than those of Cd, indicating the predominant effect of Zn and Pb on this enzyme activity under such conditions.…”
Section: Soil Microbiological Parametersmentioning
confidence: 81%
See 1 more Smart Citation
“…Although low, significant negative correlations were found between alkaline phosphatase activity values and leachable Zn and Pb contents in mine soil (|R| = 0.88 (p b 0.20) and |R| = 0.85 (p b 0.20), respectively). Similar concentrations of Zn and Cd have been reported to inhibit this enzyme activity to the same levels for most of the different soil texture types subjected to evaluation, whereas some higher concentrations are required in the case of Pb (Doelman and Haanstra, 1989;Wiatrowska et al, 2015). Mine soil Zn and Pb concentrations were about two orders of magnitude higher than those of Cd, indicating the predominant effect of Zn and Pb on this enzyme activity under such conditions.…”
Section: Soil Microbiological Parametersmentioning
confidence: 81%
“…The activity of both acid and alkaline phosphatases in soils has been shown to be inhibited by trace elements, including Zn, Pb and Cd (Tyler, 1976;Juma and Tabatabai, 1977;Doelman and Haanstra, 1989;Roy et al, 2004;Wiatrowska et al, 2015). No significant increases (p b 0.05) were produced in acid phosphatase activity after treatment with sepiolite.…”
Section: Soil Microbiological Parametersmentioning
confidence: 90%
“…However, trace elements Cr, Zn, Cu, Pb, Co, and As were not show any positive correlation with biological properties. It indicates that Cr, Zn, Cu, Pb, Co, and As trace elements were stronger inhibitory effects on soil biological properties (Wiatrowska, Komisarek, & Dluzewski, 2015).…”
Section: Soil Physico-chemical and Biological Propertiesmentioning
confidence: 96%
“…Wiatrowska et al [72] found that Dehydrogenases, acid and alkaline phosphatases exhibited the highest sensitivity toward Zn and it decreased in the order of metal concentrations: Zn > Cd > Cu > Pb. In contrast, urease was more tolerant to Zn.…”
Section: Effects Of Potentially Toxic Elements On Soil Enzyme Activitiesmentioning
confidence: 99%